Toxoplasmosis-Related Knowledge and Practices Among Pregnant Women in the United States. Issue 3 (2003) - Jones, Jeffrey L.; Ogunmodede, Folashade; Scheftel, Joni; Kirkland, Elizabeth; Lopez, Adriana; Schulkin, Jay; Lynfield, Ruth
Abstract : Background: Infection with Toxoplasma gondii during pregnancy can lead to severe illness in the fetus. Many T. gondii infections are preventable by simple hygienic measures. Methods: We surveyed pregnant women in the US to determine their knowledge about toxoplasmosis and their practices to prevent infection. Volunteer obstetricians selected to be demographically representative of the American College of Obstetricians and Gynecologists recruited the participants. Results: Of 403 women responding to the survey, 48% indicated that they had heard or seen information about toxoplasmosis; however, only 7% were aware of being tested for the disease. Forty percent of responding women knew that toxoplasmosis is caused by an infection, but 21% thought that a poison causes it. The highest level of knowledge was about cats and T. gondii ; 61% responded that the organism is shed in the feces of infected cats and 60% responded that people could acquire toxoplasmosis by changing cat litter. There was a low level of knowledge about other risk factors; only 30% of the women were aware that T. gondii may be found in raw or undercooked meat. Nevertheless, a high percentage of women indicated that they do not eat undercooked meat during pregnancy and that they practice good hygienic measures such as washing their hands after handling raw meat, gardening or changing cat litter. Conclusion: Except for the risk of transmission from cats, knowledge among pregnant women about toxoplasmosis is low. However, toxoplasmosis-preventive practices are generally good, suggesting that providers should continue to offer education about practices that help prevent foodborne diseases in general as well as information about preventing toxoplasmosis specifically.